An empirical study of online food delivery services from applications perspective. (2023) - Ramesh, R.; Venkatesa Prabhu, Sundramurthy; Sasikumar, Bashyam; Kiruthika Devi, B.S.; Prasath, P.; Praveena Rachel Kamala, S.
Abstract: The scientific advancement in urbanised locations with the relation of the lower classes and discovery to Secularized culture is boosting the growth of food delivery applications and restaurant industries in India. The convenience of users is the primary objective aspect of such, while the second thing that these software's are also beneficial for the development of the market in eating and food supply, as the use of the online platform is a place where the restaurant owner is prepared to attract as many users as he can by allowing them to see the entire food menu in accordance with item name, price, photo, etc. Apps for food delivery have proven to be a big success in India as people are very well about all its operations and services. As one can order food for any type of occasion, it is one of the most comfortable and trusted options available. This helps to save time, resources, fuel and efforts for people, which is one of the key reasons why this industry is thriving and will tend to do so. Therefore, part of my initiative would be to review the theoretical background in various aspects of food sector apps, business models and various factors affecting adoption of food delivery apps that have never been addressed before.